2010
DOI: 10.1128/aem.01059-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Catechin as One of the Flavonoids from Combretum albiflorum Bark Extract That Reduces the Production of Quorum-Sensing-Controlled Virulence Factors in Pseudomonas aeruginosa PAO1

Abstract: Quorum-sensing (QS) regulates the production of key virulence factors in Pseudomonas aeruginosa and other important pathogenic bacteria. In this report, extracts of leaves and bark of Combretum albiflorum (Tul.) Jongkind (Combretaceae) were found to quench the production of QS-dependent factors in P. aeruginosa PAO1. Chromatographic fractionation of the crude active extract generated several active fractions containing flavonoids, as shown by their typical spectral features. Purification and structural charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(245 citation statements)
references
References 93 publications
(129 reference statements)
12
230
2
1
Order By: Relevance
“…Separately, in studies of 50 medicinal plants from South Florida, six plants representing five different families were found to have QSI activity against C. violaceum and A. tumefaciens and could inhibit production of elastase, pyoverdin, and biofilms of P. aeruginosa (277,278). Several flavenoid-like compounds were found to be produced by one of these species, a member of the Combretum family, and the molecule catachin (a flavan-3-ol) was one compound isolated that accounted for these activities (136).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Separately, in studies of 50 medicinal plants from South Florida, six plants representing five different families were found to have QSI activity against C. violaceum and A. tumefaciens and could inhibit production of elastase, pyoverdin, and biofilms of P. aeruginosa (277,278). Several flavenoid-like compounds were found to be produced by one of these species, a member of the Combretum family, and the molecule catachin (a flavan-3-ol) was one compound isolated that accounted for these activities (136).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…These molecules specifically inhibited the activation of virulence genes by quorum sensing, reduced biofilm tolerance to tobramycin and also decreased virulence in a Caenorhabditis elegans pathogenesis model. In a recent study, a screening of quorum-sensing-inhibiting molecules derived from the plant species Combretum albiflorum revealed that catechin has a negative impact on the production of quorumsensing-dependent virulence factors (Vandeputte et al, 2010). Subinhibitory concentrations of macrolides have been shown to be effective in inhibiting quorum-sensingdependent virulence both in vivo and in vitro (Imamura et al, 2004;Molinari et al, 1993;Sofer et al, 1999;Tateda et al, 2001).…”
Section: M Antunes and Othersmentioning
confidence: 99%
“…Reversed-phase HPLC analysis revealed a major peak (96.673 %) (Fig. 5) detected by its absorbance at 254 nm [15]. This major peak, designated Peak 3, was subjected to further analysis.…”
Section: Purification Of Inhibitorsmentioning
confidence: 99%